Psychometric Properties of Bullying Participant Behaviors Questionnaire (BPBQ) in Adolescence – Indonesian Version - Khoirot, Umdatul; Elok fa'iz Fatma El Fahmi; Fuji Astutik; Agus Iqbal Hawabi; Muallifah; Achmad Zulkifli Adnan (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
The Bullying Participant Behaviors Questionnaire (BPBQ) is a self-report questionnaire designed to measure the various roles adolescents play in bullying situations. This study aims to evaluate the psychometric properties of the Indonesian-adapted version of the BPBQ through validity and reliability tests in a local context. The adaptation procedure was carried out systematically through the stages of translation, expert panel review, and readability testing before the questionnaire was distributed. This study involved 847 adolescents (34% male, 66% female) aged 12–18 years who were selected using convenience sampling. Confirmatory factor analysis was used to confirm the five-factor structure (perpetrator, accomplice, victim, helper, and bystander) in accordance with the previously developed theoretical model of the BPBQ. Although the model fit indices showed CFI (0.75) and TLI (0.74) values below the ideal threshold of 0.90, these results provide sufficient (acceptable) preliminary evidence in the context of research on complex behavior, supported by overall factor loadings ranging from 0.30 to 0.77. Although two items had low factor loadings (B6 = 0.31 and C10 = 0.18) after model modification via correlation among error terms, all 50 items were retained to maintain the structural integrity and cross-cultural comparability of the original BPBQ scale. The instrument’s reliability indicates excellent internal consistency (0.904), with scores for each subscale also classified as good (Perpetrator = 0.793, Perpetrator’s Accomplice = 0.828, Victim = 0.828, Defender = 0.867, Outsider = 0.861). The implications of this research are the availability of a cross-culturally valid instrument for education practitioners in Indonesia. The use of the BPBQ enables early identification of bullying group dynamics, which plays a crucial role in designing more effective school-based intervention programs—not only for victims and perpetrators but also for bystanders (perpetrator’s accomplices, defenders, and outsiders).